Adipocyte Proteins and Storage of Endogenous Fatty Acids in Visceral and Subcutaneous Adipose Tissue in Severe Obesity. Issue 6 (24th April 2021) - Lytle, Kelli A.; Bush, Nikki C.; Triay, Jessica M.; Kellogg, Todd A.; Kendrick, Michael L.; Swain, James M.; Gathaiya, Nicola W.; Hames, Kazanna C.; Jensen, Michael D.
Abstract : Objective: This study tested whether substrate concentrations or fatty acid storage proteins predict storage of endogenous lipids in visceral adipose tissue (VAT) and upper body subcutaneous adipose tissue (UBSQ) fat. Methods: The day prior to surgery, 25 patients undergoing bariatric procedures received an infusion of autologous [1‐ 14 C]triolein‐labeled very low‐density lipoprotein (VLDL) particles, and during surgery, they received a continuous [U‐ 13 C]palmitate infusion/bolus [9, 10‐ 3 H]palmitate tracer. VAT and UBSQ fat were collected to measure VLDL‐triglyceride (TG) storage, direct free fatty acid (FFA) storage rates, CD36 content, lipoprotein lipase (LPL), acyl‐CoA synthetase, diacylglycerol acetyl‐transferase, and glycerol‐3‐phosphate acyltransferase activities. Results: Storage of VLDL‐TG and FFA‐palmitate in UBSQ and VAT was not different. Plasma palmitate concentrations correlated with palmitate storage rates in UBSQ and VAT ( r = 0.46, P = 0.02 and r = 0.46, P = 0.02, respectively). In VAT, VLDL‐TG storage was correlated with VLDL concentrations ( r = 0.53, P < 0.009) and LPL ( r = 0.42, P < 0.05). In UBSQ, VLDL‐TG storage was correlated with LPL ( r = 0.42, P < 0.05). CD36, acyl‐CoA synthetase, glycerol‐3‐phosphate acyltransferase, and diacylglycerol acetyl‐transferase were not correlated with VLDL‐TG or palmitate storage. Conclusions: Adipose storage of VLDL‐TG is predicted by VLDL‐TG concentrations and LPL; FFA concentrations predict direct adipose tissue FFA storage rates.